2016
DOI: 10.1186/s13584-016-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Does dental health of 6-year-olds reflect the reform of the Israeli dental care system?

Abstract: BackgroundThe National health insurance law enacted in 1995 did not include dental care in its basket of services. Dental care for children was first included in 2010, initially up till 8 years of age. The eligibility age rose to 12 years in 2013.The dental survey of 6 year-olds in 2007 found that the average of decayed, missing and filled teeth index (dmft) was 3.31 and 35 % of children were caries free. The current cross sectional survey of dental health for 6 year-olds was conducted as a comparison to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 4 publications
2
15
0
Order By: Relevance
“…The results of the present study demonstrated that decayed primary and permanent teeth constituted a large and considerable proportion of DMFT and dmft indices, so that the proportion of filled teeth in dmft index of 7-year old was as low as 6.4% and in DMFT index of 12-year was 55.55%. A high proportion of decayed teeth observed in the present study is similar to those reported by other studies conducted in other developing and undeveloped countries such as India, Afghanistan, and Ethiopia [ 20 , 29 , 30 ] and is higher than those reported in developed countries such as Israel and Spain [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study demonstrated that decayed primary and permanent teeth constituted a large and considerable proportion of DMFT and dmft indices, so that the proportion of filled teeth in dmft index of 7-year old was as low as 6.4% and in DMFT index of 12-year was 55.55%. A high proportion of decayed teeth observed in the present study is similar to those reported by other studies conducted in other developing and undeveloped countries such as India, Afghanistan, and Ethiopia [ 20 , 29 , 30 ] and is higher than those reported in developed countries such as Israel and Spain [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…The Israeli dental system underwent substantial changes in the last decade [ 25 ]. Dental care for children was included in the National Health Insurance law.…”
Section: Discussionmentioning
confidence: 99%
“…Despite technological advancement and the development of new treatment techniques, health requirements for diseases of the oral cavity are increasing. A large number of developing countries struggle with oral cavity health problems [1][2][3]. A good oral cavity health state is a necessary condition for a healthy lifestyle, which can be influenced by oral cavity diseases such as caries [4].…”
Section: Introductionmentioning
confidence: 99%